If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 3 = 7 Reorder the terms: 3 + 5y = 7 Solving 3 + 5y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5y = 7 + -3 Combine like terms: 3 + -3 = 0 0 + 5y = 7 + -3 5y = 7 + -3 Combine like terms: 7 + -3 = 4 5y = 4 Divide each side by '5'. y = 0.8 Simplifying y = 0.8
| 34=5x^2-13x+6 | | 6+2k-3b+8k+8+6b= | | 7n+2n=72 | | -18x-4x=2 | | x*3x=675 | | 0=-16t^2+220t+100 | | n-14.7=5.68 | | -18-4x=2 | | 45x^2-56x+16=0 | | 9x^2+41x-20=0 | | -3.49+m=-2.67 | | -7(4b+4)+(29b-1)=0 | | 10n+20=2n-4 | | 3.8q-2.8-5.4q=-2.6q-5.4 | | 0=81z^2-49 | | 2v+18=16-4(v+8) | | t+10=7z+4 | | 6m^2-8m= | | 15x+22(x-4)=282 | | 81y^2-16=0 | | 15x+22(x-3)=489 | | (12-3+5k)6+4k-2(k+5)= | | 6x-4(x+1)=2x+4 | | n^2+2n=3 | | 16-2t=2+2t | | 2m^2-50=0 | | r^2+12=-7r | | 12+6b=2b | | b^2+56=-15b | | 3x-2=1.2x | | 6y^4+7y^3-37y^2-8y+12=0 | | 2m+23=9m-5 |